(untitled) - Alerich, Walter N. (New York, N.Y., 2006)
With a highly practical approach, Electric Motor Control, 8E provides a useful and effective tool for anyone who will install, monitor, and/or maintain motor controls. The book begins by introducing the simplest of equipment and then builds upon this knowledge, step-by-step, enabling readers to learn how to draw and interpret motor control schematic diagrams. Subsequent units provide useful information on motor control components and how they are connected to form complete control circuits.
Keywords: Electric controllers,Electric motors